The instructional design trainer's guide : authentic practices and considerations for mentoring ID and ED tech professionals - Stefaniak, Jill E., 1984-; Reese, Rebecca M. (New York, NY : Routledge, 2022)
"The Instructional Design Trainer's Guide provides foundational concepts and actionable strategies for training and mentoring instructional design and educational technology students to be effective across contexts. ID faculty are charged with bridging the gap between research and practice preparing graduate students for the real-world workforce. This book provides trainers and university programs with authentic learning experiences that better articulate the practices of and demands on design and technology professionals in the field. Through this enhanced perspective, learners will be better positioned to confidently embrace constraints, work among changing project expectations, interact with multiple stakeholders, and convey to employers the skills and competencies gleaned from their formal preparation"--
Instructional design embedded in culture / Beth Sockman and Laura Kieselbach -- Preparing instructional designers to scale needs assessment / Jill E. Stefaniak, Lisa Giacumo, and Steve Villachica -- The value of human performance improvement in instructional design and technology / T. Logan Arrington, Alison L. Moore, Kaila Steele, and James D. Klein -- Preparing instructional designers to apply human performance technology in global context / Lisa A. Giacumo and Tutaleni I. Asino -- Integrating evaluation in instructional design practice / Philena DeVaughn -- Project management for instructional designers : navigating people, processes, and politics / Shahron Williams van Rooij -- Supporting instructional design graduate education through networked learning and institutional social media / Enilda Romero-Hall -- Creating and cultivating a regional community of practice for instructional design and faculty development practitioners / Samantha J. Blevins, Tracey W. Smith, Charley Cosmato, M. Aaron Bond, and Emory Maiden -- Developing consulting skills in novice instructional designers / Barbara B. Lockee and Miriam B. Larson.
Keywords: Instructional systems -- Design; Educational technology; EDUCATION / Distance Education & Learning; EDUCATION / Computers & Technology; EDUCATION / Professional Development